PENGARUH GDP TERHADAP INFLASI DI INDONESIA: TAHUN 2000-2012 - Darmayanti, Novi (JURNAL MANAJEMEN DAN AKUNTANSI, 2014)
The purpose of this study was to determine the GDP to inflation in Indonesia in 2000-2012. The data used in this analysis are secondary data of monthly GDP and Inflation 2000-2012 period. Methods of analysis using descriptive and econometric analysis to test data analysis techniques Stationary. The analysis showed that Indonesias GDP growth from 2000 to 2009 showed uptrend, although GDP growth had declined in 2001. The existence of the rising trend of GDP growth is in line with the rising trend of IHSG. Keywords: Inflation, Stationary, GDP, GDP,IHSG